Recent advances in bacterial therapeutics based on sense and response - Zhuo Feng; Yuchen Wang; Haiheng Xu; Yunfei Guo; Wen Xia; Chenxuan Zhao; Xiaozhi Zhao; Jinhui Wu (Elsevier, 2023)
Intelligent drug delivery is a promising strategy for cancer therapies. In recent years, with the rapid development of synthetic biology, some properties of bacteria, such as gene operability, excellent tumor colonization ability, and host-independent structure, make them ideal intelligent drug carriers and have attracted extensive attention. By implanting condition-responsive elements or gene circuits into bacteria, they can synthesize or release drugs by sensing stimuli. Therefore, compared with traditional drug delivery, the usage of bacteria for drug loading has better targeting ability and controllability, and can cope with the complex delivery environment of the body to achieve the intelligent delivery of drugs. This review mainly introduces the development of bacterial-based drug delivery carriers, including mechanisms of bacterial targeting to tumor colonization, gene deletions or mutations, environment-responsive elements, and gene circuits. Meanwhile, we summarize the challenges and prospects faced by bacteria in clinical research, and hope to provide ideas for clinical translation.